PEMANFAATAN PLATFORM WAYGROUND SEBAGAI ALAT PENILAIAN PEMBELAJARAN DIGITAL BAGI SISWA DI SMKN 1 KOTA SERANG - Salwa Nur Azizah; Nadia Ayu Lestari; Dede Putri; Abid Abdillah; Diva Anggun Audia; Hamidah Hamidah; Dede Yana; ⁠Eri Achriyanti; ⁠Farah Rizki Nabillah (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2026)
This study examines how SMKN 1 Kota Serang uses the Wayground platform as a digital learning assessment tool. The use of digital platforms is an efficient way to overcome various challenges faced by traditional evaluation methods due to advances in information technology. Wayground provides interactive features that increase student participation and facilitate teacher assessment. Findings indicate that utilizing Wayground can increase motivation and the effectiveness of learning assessment, despite challenges such as dependence on internet connectivity and limited device availability. In an effort to improve the education system in the digital era, this paper outlines the advantages and disadvantages of using digital platforms for evaluation